Psychometric Analysis of Capacity of Forgiveness Scale in Arequipa - Arias Gallegos, Walter L. (2022)
Forgiveness is a construct that is being investigated with great interest by psychologists, but this requires having validated instruments. María Casullo’s Capacity to Forgive Assessment Scale (CAPER) is one of the first test crated in Latin America to measure forgiveness. The objective of this study is to analyze the psychometric properties of the CAPER in a sample of 163 people from the city of Arequipa, who were selected using non-probabilistic methods. The results indicate that the internal structure of the test has three factors (Forgiveness to situations, Forgiveness to others, and Forgiveness to oneself) calculated by means of confirmatory factor analysis; but the internal consistency indexes for each of the three dimensions indicate low reliability, with coefficients less than .7, using Cronbach´s Alpha test and McDonald’s Omega test. Therefore, a cautious use of this instrument is recommended, and further study of its psychometric properties.